Wage differentials, industrial and skill structures in Malaysian manufactures, 1974-1996 - Said, Rusmawati; Abdul Rashid, Zakariah (Universiti Utara Malaysia, 2003)
The objective of the present paper is to measure the proportional changes in salaries and wages and the impact of changing industrial structure on the employment of skill workers in Malaysian manufactures during 1974-1996. By using 5-digit MIC, 30 major groups of industivies are chosen out of 129 sub-industries. The proportional change in relative wage is ascribed to three distinct efects, namely distributional, diferential and industrial ranking effects. The present paper found that during the overall period, there was a clear trend of skill widening ascribed mainly to distribution of skill among sub-industries while skill diferences within sub-industry seem to be unimportant. Among all the industries, electrical machinery industry seems to be the most important industry that caused major skill differentials.